Research of physical and chemical characteristics of large fillers for production of ferro-concrete sleepers - Rybkin, V. V.; Kovalenko, V. V.; Zayats, Yu. L.; Pshinko, P. O.; Lisnyak, V. P.; Yaryshkina, L. O.; Vasilyeva, S. V.; Kovalenko, S. V. (Science and Transport Progress, 2012)
The paper is dealt with an analysis of the reactivity of large fillers and their fractional composition for the production of ferro-concrete sleepers.